POLA ASUH ORANGTUA DALAM MEMBENTUK AKHLAK ANAK USIA DINI - Khoirul Ummah; Ika Ratih Sulistiani; Ika Anggraheni (UNISMA, 2020)
The purpose of this study is to describe parenting patterns in shaping the morals of early childhood in the Takeran Hamlet. This research method is a field research with a qualitative research approach. Data collection techniques using observation, interviews and documentation in the form of photos. The data analysis technique used at the time of the study was the descriptive analysis method and content study. The data source is the activities of parents and early childhood in the Takeran Hamlet. From the results obtained by researchers can draw conclusions that in shaping the morals of early childhood children need parenting and active role of parents. This means that the good and bad behavior of children depends on the parents' concerns about children's education, including physical and spiritual. Thus the responsibility of parents to their children is not just fulfilling physical needs but also spiritual needs that must be met by parents because it really determines the good behavior of children and in the midst of society is also good.